Character Education in Lembaga Dakwah Kampus - bustomi, ahmad (STAI Ma'had Aly Al-Hikam Malang, 2022)
AbstractThis Research began from a personal experiences of researcher about students who have thought that the democration is Kafir product and Indonesia which is majority is Islamic should not agree with Democracy, Pancasila and Constitution. The recruitment curriculum of cadre is very important thing to be analyzed more deeply considering from where it will be seen the direction of this students’ movement working, the background and spirit of organizations. Therefore, the researcher focuses on something important to be analyzed especially related to the role of Islamic student organization of extra campus on the forming of students’ character of LDK cadre in UIN Sunan Kalijaga. The aim of this research for describe the implementation and implication of Islamic student organization of extra University in the forming of student characters. The research using a qualitative approach and the subject of research namely of Muhammad Akhyar as Leader of LDK UIN Sunan Kalijaga. The methods of data collection used observation, interview and documentation. Data analysis in this research uses Milles Huberman model with data reduction technique, data presentation, and conclusion. The results of this research show that: Firstly, The implementation of cadre curriculum LDK is as the method which has Guide in TEKAD called MC Instructor whose duty give introduction before presenter, guides the learning process in class and fgd/fanel companion, while the speakers is called the instructor. The method of study which consists of speech method, Interactive, fgd/sgd, panel, group dynamics and debate. Secondly, the impilication of curriculum shows nine characters: religious, tolerance, discipline, hard work, creative, democratic, friendly/communicative, social care and responsible.Keywords: Student Character, Recruitment Curriculum. AbstrakPenelitian ini bermula dari pengalaman pribadi peneliti mengenai maraknya mahasiswa yang berfikiran that demokrasi adalah produk kafir dan tidak sepatutnya Indonesia yang mayoritas rakyatnya beragama Islam menyepakati demokrasi, pancasila dan undang-undang. Kurikulum perkaderan menjadi hal yang paling pokok untuk dikaji lebih, mengingat dari sanalah akan terlihat arah gerakan mahasiswa ini berjalan, latar belakangnya serta spirit berorganisasinya. Oleh karena itu penting untuk dikaji terutama terkait peran kurikulum perkaderan LDK UIN Sunan Kalijaga dalam pembentukkan karakter mahasiswa. Tujuan penelitian ini untuk mendeskripsikan pelaksanaan dan pengaruh organisasi mahasiswa Islam ekstra kampus dalam pembentukan karakter mahasiswa. Penelitian menggunakan pendekatan kualitatif dan subjek penelitiannya adalah Muhammad Akhyar selaku Ketua Umum LDK. Metode pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Analisis data pada penelitian ini menggunakan model Milles Huberman dengan teknik reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: Pertama, Implementasi kurikulum pengkaderan LDK yaitu dengan metode memiliki Pemandu dalam TEKAD, yang disebut instruktur MC, bertugas memberikan pengantar sebelum pemateri memberi materi, memandu jalannya kelas dan pendamping fgd/panel, sedangkan pemateri disebut instruktur. Metode yang digunakan adalah metode ceramah, tanya jawab, fgd/sgd, panel, dinamika grup dan debat. Kedua, peran kurikulum memunculkan 9 karakter, yaitu religius, toleransi, disiplin, kerja keras, kreatif, demokratis, bersahabat/komunikatif, peduli sosial dan tanggung jawab.Kata Kunci: Karakter Mahasiswa, Kurikulum Pengkaderan.